Is dangerousness a myth?: injuries and police encounters with people with mental Illnesses - Morabito, Melissa Schaefer (Criminology & public policy, 2015)
This study examined all “use-of-force” reports collected by the Portland Police Bureau in Portland, Oregon, between 2008 and 2011, to determine whether their encounters with people with mental illnesses are more likely to result in injury to officers or subjects when force is used. Although several factors significantly predicted the likelihood of injury to either subjects or officers, mental illness was not one of them.